2019
DOI: 10.1002/uog.20244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of placenta previa with placenta accreta spectrum disorder on fetal growth

Abstract: Objectives To evaluate fetal growth in pregnancies complicated by placenta previa with or without placenta accreta spectrum (PAS) disorder, compared with in pregnancies with a low‐lying placenta. Methods This was a multicenter retrospective cohort study of singleton pregnancies complicated by placenta previa with or without PAS disorder, for which maternal characteristics, ultrasound‐estimated fetal weight and birth weight were available. Four maternal–fetal medicine units participated in data collection of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
6
20
0
1
Order By: Relevance
“…low-lying placenta (partial previa) and placenta previa (marginal or complete) did not impact the risk of FGR. These data and our recent study showing no difference in the rate of FGR in both low-lying and placenta previa [31] suggest that implantation in the lower uterine segment does not affect the normal development of the uteroplacental circulation and/or normal placental functions.…”
Section: Low-lying Placenta and Placenta Previasupporting
confidence: 72%
See 1 more Smart Citation
“…low-lying placenta (partial previa) and placenta previa (marginal or complete) did not impact the risk of FGR. These data and our recent study showing no difference in the rate of FGR in both low-lying and placenta previa [31] suggest that implantation in the lower uterine segment does not affect the normal development of the uteroplacental circulation and/or normal placental functions.…”
Section: Low-lying Placenta and Placenta Previasupporting
confidence: 72%
“…The pathological and phenotypic changes are hard to define as the normal vascular architecture of the placental bed may be distorted in the scar area. Furthermore, these changes in remodelling of the utero-placental circulation in placenta accreta are not associated with any impact on placental or fetal growth, nor on the incidence of pre-eclampsia [31].…”
Section: Accreta Placentationmentioning
confidence: 91%
“…A meta-analysis showed that placenta previa was associated with a mild increase in the risk of intrauterine growth restriction [29]. Jauniaux et al found no difference in fetal growth between women with placenta previa and PAS disorders and women with placenta previa only [30]. The effects of placenta previa on the neonatal outcomes in subsequent pregnancies have seldom been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies including Moradan et al (2018) and Barzegar Jalali (2016) have also been consistent with our study (22,23) but in some studies, different findings have been reported and a significant relationship between cesarean and placenta previa history was not reported (24,25). Many studies have indicated the presence of risk factors and demographic characteristics associated with placenta previa or placental abruption that the role of risk factors in the identification and reduction of complications have been highlighted (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%